Solution structure of zinc-seamed C-alkylpyrogallol[4]arene dimeric nanocapsules. Issue 6 (15th January 2021) - Kumari, Harshita; Wycoff, Wei G.; M. Mayhan, Collin; Kline, Steven R.; So, Joshua R.; Deakyne, Carol A.; Adams, John E.; Atwood, Jerry L.
Abstract : Solid-state core geometry of zinc-seamed C -propylpyrogallol[4]arene dimers is retained in solution; however, external ligands exchange with solvent molecules. Abstract : The structural stability and solution geometry of zinc-seamed- C -propylpyrogallol[4]arene dimers has been studied in solution using in situ neutron scattering and 2D-DOSY NMR methods. In comparison with the structures of the analogous copper-/nickel-seamed dimeric entities, the spherical geometry of the PgC3 Zn species ( R = 9.4 Å; diffusion coefficient = 1.05 × 10 −10 m 2 s −1 ) is larger due to the presence of ligands at the periphery in solution. This enhanced radius in solution due to ligation is also consistent with the findings of model molecular dynamics simulations of the zinc-seamed dimers.